If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 7 = 7x + -19 Reorder the terms: 7 + -6x = 7x + -19 Reorder the terms: 7 + -6x = -19 + 7x Solving 7 + -6x = -19 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + -6x + -7x = -19 + 7x + -7x Combine like terms: -6x + -7x = -13x 7 + -13x = -19 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -13x = -19 + 0 7 + -13x = -19 Add '-7' to each side of the equation. 7 + -7 + -13x = -19 + -7 Combine like terms: 7 + -7 = 0 0 + -13x = -19 + -7 -13x = -19 + -7 Combine like terms: -19 + -7 = -26 -13x = -26 Divide each side by '-13'. x = 2 Simplifying x = 2
| 3=a/5-9 | | 4x+7(-4x-28)=20 | | 19y+43=81 | | -824=8(-15x+2) | | 7-2.59= | | -154=-8r-10 | | 3(t+4)-2(2*t+3)=-4 | | -12n+25=-14 | | A+a+a+60=180 | | 7x-17=2x-2 | | -10x+355=-163-3x | | 4x-13=1+x-4 | | 3x+4i=6-2yi | | (5x^4*y^4+28x^6)dx+(4x^5*y^3-3y^2)dy=0 | | -11=4(-2)-3 | | 20+43=17+x | | -28+0.3x=-23 | | 14=3x-x-10 | | 7-p=4 | | 90*23=x | | 60=0.5x+32 | | 7/x-5=6 | | (b+3)(b^2+2b+1)=0 | | 5y^2+10y-48=0 | | 24+0.79=1.19x | | 9=4(-3)-3 | | -14(-10x-13)=1162 | | -24+7x=25 | | 2x22/7x25x3.5 | | 4x^6+11x^5-x^3+7x+7=0 | | 3x-6(6x+31)=12 | | 2*x=512 |